2003
DOI: 10.1149/1.1596163
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Near-Eutectic SnAg Solders for Wafer-Level Packaging

Abstract: The electrodeposition of near-eutectic SnAg solders for wafer level packaging was investigated with Shipley-Ronal’s EXP-0700 SnAg bath. Fundamental studies including polarization behavior, morphological transition, and compositional change were performed to investigate the alloy deposition mechanism. It was proven that the mass transfer limitation of silver ions at low potential drove the drastic change of morphology and composition with increasing current density. The morphological transition occurred through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…4 demonstrates the Ag content in the Sn-Ag bumps plated for 20 min, where the current density was changed from −40 to −60 mA/cm 2 . The Ag content decreased with increasing current density because the deposition potential of Ag is higher than that of Sn, and more Ag was deposited at a lower current density [16], [29]. In addition, Joseph et al [30] and Jang et al [31] reported that when the current density was higher, the fluxes of Sn ions were stronger than that of the noble ion, which resulted in a lower Ag content of the deposits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 demonstrates the Ag content in the Sn-Ag bumps plated for 20 min, where the current density was changed from −40 to −60 mA/cm 2 . The Ag content decreased with increasing current density because the deposition potential of Ag is higher than that of Sn, and more Ag was deposited at a lower current density [16], [29]. In addition, Joseph et al [30] and Jang et al [31] reported that when the current density was higher, the fluxes of Sn ions were stronger than that of the noble ion, which resulted in a lower Ag content of the deposits.…”
Section: Resultsmentioning
confidence: 99%
“…The Sn-Ag-Cu alloy [13], [14] has reliable mechanical properties, but producing a ternary alloy with a desired composition is relatively difficult to achieve by electroplating. Among the bumping materials, Sn-Ag [15]- [22] is popular compared to other metal alloys owing to its good creep resistance, thermomechanical fatigue behavior [16], comparable shear strength to that of conventional Sn-Pb [20], and greater connection reliability [17], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Its higher melting temperature and superior thermal fatigue property make it a good candidate for automotive and flip-chip applications. This realization motivated researchers in industrial laboratories as well as academia to develop a number of commercially viable tin-silver plating processes [92,93,[99][100][101][102][103][104][105][106][107].…”
Section: Electrodeposition and Materials Properties Of Electrodepositementioning
confidence: 99%
“…Among these methods, electroplating is the most popular. Many prior studies related to this method have been conducted [5,6,[9][10][11][12][13]. Much interest has been generated by lead-free Sn-based alloys as bumping materials, and Sn-Ag [5,10,[12][13][14][15][16][17], Sn-Cu [11], and Sn-Ag-Cu [18,19] electroplating approaches have been investigated.…”
Section: Introductionmentioning
confidence: 99%